Discovery and understanding of novel mechanisms to improve insulin resistance, obesity and type 2 diabetes mellitus (T2DM) by targeting branched chain amino acid metabolism - Ramzan, Imran (2023)
Obesity and type 2 diabetes (T2DM) are major health problems in the UK and globally. Yet interventions for obesity and T2DM are limited to exercise, dietary advice aimed at weight loss and control of blood sugar, and the prescription of glucose lowering drug(s). The aim of our research was to explore effects of a novel intervention, aimed at manipulating the blood levels of three specific amino acids called the branched-chain amino acids (BCAAs). The abundance of these BCAAs is higher in the bloodstream of people with obesity, pre-diabetes and T2DM. Recent controversies have emerged with studies speculating that higher levels of BCAAs are a cause, rather than a consequence of insulin resistance (which is the main pre-requisite in the development of T2DM).